Diseño y construcción de un prototipo de telemetría para la automatización inalámbrica del consumo de agua mensual mediante la red gsm. Caso práctico Universidad Nacional de Loja. - Medina Sucunuta, María Esther (2015)
The present thesis is based on the design, development and construction of a telemetric prototype in order to obtain water consumption data and consequently send this information to the virtual platform using GSM/GPRS network. Basically, the project is divided into two parts: hardware and software. Concerning the software part, a detailed analysis of different components was done in order to obtain data. A torrent sensor was applied through which we will obtain the quantity of gas consumption in liters/ per minutes. After this, each Arduino card was analyzed to determine which would adapt best to the telemetric system to achieve data acquisition. To send the data to the web, it was necessary to use a shield GSM/GPRS card, since this is a stablished network and some saving in the installation work will take place. To visualize the water consumption pattern that the sensor provides, we used the Arduino LCD Keypad shield. Concerning the software design, programmed language from the Arduino platform was used, which counts with an open language code. To do this, four algorithms were used: acquisition of data from the Arduino sensor, Shield GPS/GPRS card settings which will allow to connect to the internet, water fluid calculus and data sending. For the transmission of data to the server the server emoncms.org used , it is a platform "open source" that enables remote monitoring of a device which takes data variables of temperature sensors, flow, power , flow moisture , etc. Plus you have a history of daily, monthly or annual consummation you can display the graph of monitoring variables, the prototype allows acquisition and records consumption data .